Strategi inovatif dalam meningkatkan literasi dan numerasi siswa sekolah dasar di era digital - Windy Audia; Imas Mastoah (Universitas Sebelas Maret, 2025)
Literacy and numeracy are essential skills for academic success and cognitive development, especially in the 21st century. Literacy involves not only reading and writing but also critical thinking and digital comprehension, while numeracy focuses on understanding and applying mathematical concepts in daily life. The rapid advancement of digital technology demands that students acquire 21st-century skills, yet studies indicate that literacy and numeracy levels among elementary students remain low. This study aims to explore innovative strategies to improve literacy and numeracy in the digital era using a qualitative descriptive approach through literature reviews and teacher interviews. Findings suggest that integrating technology into learning, such as gamification, project-based learning, and digital media, significantly enhances student engagement, understanding, and motivation. Additionally, flipped classrooms and collaborative learning promote interactive, student-centered education. The study highlights the importance of teacher training and parental involvement in optimizing digital education. Implementing these strategies can equip students with essential literacy and numeracy competencies, preparing them for technological advancements and global educational standards.